Hydrogeochemical Characteristics and Quality Assessment of Groundwater in Semi-Arid Region of District Mianwali, Pakistan: A Multivariate Statistics Approach - Asim, M.; Iqbal, N.; Rafiq, M.; Ghaffar, A. (The Nucleus, 2020)
Hydrogeochemical characterization and groundwater quality assessment in terms of suitability for domestic and irrigation purposes of Piplan area, district Mianwali has been investigated. Three major hydrogeochemical facies (Ca-Mg-HCO3 > Na-HCO3 > Ca-Mg-Cl) are identified by Piper’s diagram. The dominant hydrogeochemical facies, Ca-Mg-HCO3 suggested fresh recharge to groundwater. To recognize the defining processes of hydrogeochemistry, Gibbs diagram plays a vital role by ascertaining the water-rock interaction; whereas, silicate weathering is recognized as a primary source of mineral dissolution with dolomite (CaMg(CO3)2) as the major geochemical phase. The Physico-chemical and chemical parameters such as pH, EC, TDS, Ca, Mg, Na, K, HCO3, Cl, SO4 and NO3 were employed to substantiate groundwater quality. Overall water quality of the study area is found admissible in comparison to World Health Organization (WHO) and Pakistan Standard Quality Control Authority (PSQCA) standards for drinking as well as domestic consumption. On the other hand, quality of irrigation water is generally well below the permissible limits of irrigation suitability indices such as sodium percentage (Na%), sodium adsorption ratio (SAR), permeability index (PI and Kelly’s ratio (KR), except the residual sodium carbonate (RSC) and magnesium hazard (MH). Principal component analysis (PCA) revealed mineral dissolution and rock weathering as the distinctive phenomena controlling groundwater chemistry and groundwater pollution by anthropogenic sources.